A developmental delay linked missense mutation in Kalirin-7 disrupts protein function and neuronal morphology - Parnell, Euan; Voorn, Roos A.; Martin-de-Saavedra, M. Dolores; Loizzo, Daniel D.; Dos Santos, Marc; Penzes, Peter (Frontiers in Molecular Neuroscience, 2022)
The Rac1 guanine exchange factor Kalirin-7 is a key regulator of dendritic spine morphology, LTP and dendritic arborization. Kalirin-7 dysfunction and genetic variation has been extensively linked to various neurodevelopmental and neurodegenerative disorders. Here we characterize a Kalirin-7 missense mutation, glu1577lys (E1577K), identified in a patient with severe developmental delay. The E1577K point mutation is located within the catalytic domain of Kalirin-7, and results in a robust reduction in Kalirin-7 Rac1 Guanosine exchange factor activity. In contrast to wild type Kalirin-7, the E1577K mutant failed to drive dendritic arborization, spine density, NMDAr targeting to, and activity within, spines. Together these results indicate that reduced Rac1-GEF activity as result of E1577K mutation impairs neuroarchitecture, connectivity and NMDAr activity, and is a likely contributor to impaired neurodevelopment in a patient with developmental delay.